Plasma Myokine Concentrations After Acute Exercise in Non-obese and Obese Sedentary Women - Garneau, Léa; Parsons, Stephanie A.; Smith, Steven R.; Mulvihill, Erin E.; Sparks, Lauren M.; Aguer, Céline (Frontiers in Physiology, 2020)
Exercise and physical activity levels influence myokine release from skeletal muscle and contribute to circulating concentrations. Indeed, many myokines, including interleukin (IL-) 6, IL-15, secreted protein acidic rich in cysteine (SPARC) and fibroblast growth factor (FGF) 21 are higher in the circulation after an exercise bout. Since these peptides modulate muscle metabolism and can also be targeted towards other tissues to induce adaptations to energy demand, they are of great interest regarding metabolic diseases. Therefore, we set out to compare, in 6 women with obesity (BMI  30kg/m2) and 5 healthy women (BMI 22-29.9 kg/m2), the effect of an acute bout of moderate-intensity, continuous cycling exercise (60 minutes 60% VO2peak) on the release of myokines (IL-6, IL-8, IL-10, IL-13, IL-15, SPARC and FGF21) in plasma for a 24h time-course. We found that plasma IL-8 and SPARC levels were reduced in the group of women with obesity, whereas plasma IL-13 concentrations were elevated in comparison to non-obese women both before and after the exercise bout. We also found that plasma FGF21 concentration during the 24h following the bout of exercise was regulated differently in the non-obese in comparison to obese women. Plasma concentrations of FGF21, IL-6, IL-8, IL-15 and IL-18 were regulated by acute exercise. Our results confirm the results of others concerning exercise regulation of circulating myokines, while providing insight into the time-course of myokine release in circulation after an acute exercise bout and the differences in circulating myokines after exercise in women with or without obesity.